Training, performance, and physiological predictors of a successful elite senior career in junior competitive road cyclists - Svendsen, I. S.; Tonnesen, E.; Tjelta, L. I.; Oern, S. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine whether training, performance, or physiological variables at age 18 can predict which athletes become World Tour (WT) riders at senior level. Methods: Based on performance level at age 23, 80 competitive male cyclists were retrospectively categorized into 4 groups: retired (n=21), club (n=26), continental (n=24), or WT (n=9). Data collected at age 18 were analyzed to determine whether training, performance, or physiological variables differed significantly between groups. Results: At age 23, 9 riders (11%) were WT level. These riders competed significantly more at age 18 than athletes who were club level (91.5 [19.1] h vs 62.8 [21.8] h, P=.032) or retired by age 23 (61.8 [23.4] h, P=.014). WT athletes placed significantly better in national road championships at age 18 than did continental, club, and retired athletes (all P<.01). Receiver-operating-characteristic analysis showed that placing at national championships at age 18 had good accuracy in predicting whether the athlete would later reach WT level (area under the curve =0.882). WT athletes had significantly higher maximal aerobic power at age 18 than athletes who did not reach WT level (533 [23] vs 451 [41] W and 6.9 [0.4] vs 6.2 [0.4] W/kg, P<.05). Conclusion: Already at junior level, there were performance and physiological differences distinguishing those who later became WT riders. The findings emphasize the need for high volumes of training and competition, as well as a high level of race performance already at junior level, to become a successful elite road cyclist.